Relationships between Carbon Dioxide, Malate, and Nitrate Accumulation and Reduction in Corn (Zea mays L.) Seedlings - Neyra, Carlos A. (1976)
The observation that exposure of the leaf canopy to increasing concentrations of CO(2) (100-400 μl/l) decreases the influx of nitrate to the leaf blades, but not to the roots or stalks (largely leaf sheaths), was reconfirmed using (15)NO(3)(−). Decreases in leaf nitrate supply were associated with decreases in induction of nitrate reductase, thus supporting the view that the influx of nitrate to a tissue is a major factor in regulation of the level of nitrate reductase. The whole plant (15)N distribution data show that the CO(2) effects were due to decreased influx of nitrate into the leaf blade rather than CO(2)-enhanced nitrate reduction. The decreases in nitrate accumulation by the leaf blade with increases in CO(2) concentration were only partially accounted for by differences in transpiration. Because the initial malate concentration of root tissue (detopped plants) had no subsequent effect on nitrate uptake, it seems unlikely that high levels of malate induced by CO(2) were responsible for the exclusion of nitrate from the leaf blades. Time course changes in nitrate and malate concentrations in root tissue (detopped plants) during nitrate uptake showed that oxidation of extra malate does not stimulate nitrate uptake and that malate is not specifically required as an energy source at the ion carrier level. The observation that nitrate and malate concentrations in corn leaf blades were negatively correlated was reconfirmed with 25 additional corn genotypes. However, using the same tissue, a higher correlation was obtained between malate plus aconitate and nitrate, suggesting that organic acids other than malate could be involved. The proposal that reduction of nitrate in the leaf is stoichiometrically related to malate production is a valid explanation of the relationship only if malate oxidation does not provide NADH for nitrate reduction. However, addition of malate and NAD to crude extracts (in vitro assay) or malate to leaf blade sections (in vivo assay) caused nitrate reduction. Because of these observations and the known intracellular location of NAD-malate dehydrogenase and nitrate reductase, we believe that malate oxidation is one of the major sources of NADH for nitrate reduction in corn leaf blades in situ.